2012
DOI: 10.1051/fruits/2012024
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and range of fruit fly (Diptera: Tephritidae) host plants in orchards in Niayes and the Thiès Plateau (Senegal)

Abstract: Seasonality and range of fruit fly (Diptera: Tephritidae) host plants in orchards in Niayes and the Thiès Plateau (Senegal).Abstract -Introduction. Senegal produces up to 150,000 t of fruit, of which 60,000 t are mangoes. Fruit production is important for the Niayes region, where 60% of total production is of mangoes, with citrus production coming next at 24%. Mango losses have become more substantial since the arrival of Bactrocera invadens in Senegal. The pest population increases in the mango ripening perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 17 publications
(20 reference statements)
1
28
1
1
Order By: Relevance
“…For mid-and late mango cultivars, Bactrocera invadens caused more than 90% of the damage in both Southern Sudan and Northern Sudan zones [4,27]. In the Sahelian zone (in Senegal-Niayes), Bactrocera invadens was considered to be the principal pest for mangoes during the rainy season [3,10,28]. Previous studies J.-F. Vayssières et al indicated that, in the Forest zone [29,30] and in the Guinean Savanna zone (GuineaKindia [31]), the impact of B. invadens was high during the whole mango season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mid-and late mango cultivars, Bactrocera invadens caused more than 90% of the damage in both Southern Sudan and Northern Sudan zones [4,27]. In the Sahelian zone (in Senegal-Niayes), Bactrocera invadens was considered to be the principal pest for mangoes during the rainy season [3,10,28]. Previous studies J.-F. Vayssières et al indicated that, in the Forest zone [29,30] and in the Guinean Savanna zone (GuineaKindia [31]), the impact of B. invadens was high during the whole mango season.…”
Section: Discussionmentioning
confidence: 99%
“…The mango exports from West Africa were estimated at between 35 000 t and 40 000 t, equivalent to US$ 45 M [2]. In Senegal, for example, the production of fruits was estimated at 150 000 t per year, of which 60 000 t are mango alone [1,3], with 6 000 t exported to the European Union (EU). Africa has the potential to increase mango quality and the volume of exports, and competes against the main world mango exporters for the European market.…”
Section: Introductionmentioning
confidence: 99%
“…Vayssières et al identified four types of systems in West Africa: the "gatherer production system", "production system under improvement", "more intensive production system" and "large industrialized orchards" [9]. In two other studies carried out in the Niayes region in Senegal, Vayssières et al simply differentiated between "mixed (pluri-specific)" and "homogeneous (monospecific) orchards" [6], while Ndiaye et al differentiated between "traditional" and "modern (intensive) orchards" [10]. However, these approaches were not based on a comprehensive and quantitative analysis of both the orchard designs issuing from farmers' planting choices and the agricultural practices the farmers use for current orchard management.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20]. Regarding mango production, only some studies have outlined system characterizations, which focused primarily on the level of intensification of cropping systems [6,9] and the composition of the orchards [10]. Vayssières et al identified four types of systems in West Africa: the "gatherer production system", "production system under improvement", "more intensive production system" and "large industrialized orchards" [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation